DI-008 Human Papillomavirus vaccine safety: adverse events reports in Azienda Sanitaria Provinciale Siracusa, Italy. (24th February 2014) - Avola, N; Guzzardi, S; Spadaro, D; Marletta, E; Valerio, A; Regolo, S; Sgarlata, D
Abstract : Background: In Azienda Sanitaria Provinciale (ASP) Siracusa Gardasil is the vaccine administered against HPV. Gardasil, a quadrivalent vaccine, contains antigens from double-stranded DNA virus. It has limited post-marketing experience, so its safety in administration is uncertain. Purpose: To acquire and update information on adverse Gardasil events. Materials and methods: The authors collected Adverse Drug Reaction (ADR) reports, which were received from 01/01/2009 to 31/05/2013, from all ASP Siracusa vaccination centres related to vaccines administered in the same time interval. Results: In ASP Siracusa vaccination centres, from 01/01/2009 to 31/05/2013, 19, 574 doses of vaccine were administered and there were 9 reports of ADRs (8 non-serious and 1 serious). They involved 3 children of eleven, 5 of twelve and 1 of eighteen years old. The reports were of: Neck pain, syncope and vomiting, Sweating and syncope, Sweating, syncope and dizziness, Fatigue, nausea, pallor and fainting, Hyperaemia, oedema, and pain at administration site (second dose of Varilrix was also administered), Headache, Neck and back pain and nausea for 2 days, Loss of consciousness (severe); Pyrexia (39.8°C) with headache and pains mainly in the lower limbs (at the third administered dose). There were 575 ADR associated with Gardasil administrations, collected from the Pharmacovigilance National Network (PNN) from 01/01/2009 to 31/05/2013. These consisted of: 43.3% central nervous system disorders, 39.1% systemic disorders and administration site conditions, 23.5% skin and subcutaneous tissue diseases, 17.4% gastrointestinal disease 12% musculoskeletal system and connective tissue diseases. Conclusions: The reporting rate between 01/01/2009 to 31/05/2013, in ASP Siracusa, was 0.46/1.000 administered doses. The ADRs reports in ASP Siracusa highlight a high incidence of central nervous system symptoms (cervical pain, syncope, sweating, weakness, paleness, dizziness, headache), according to ADRs collected in PNN and don't show warning signs other than those already recorded by the regulatory authorities. No conflict of interest.